1996
DOI: 10.1093/oxfordjournals.humrep.a019159
|View full text |Cite
|
Sign up to set email alerts
|

Psychology: A comparison of single and married recipients of donor insemination

Abstract: There has been some controversy surrounding the use of donor insemination (DI) for single women. The purpose of the present study was to compare psychological characteristics of married versus single women who were DI recipients. A total of 17 single women and 17 married women completed psychological questionnaires regarding psychiatric symptomatology, self-esteem, and their attitudes towards DI prior to treatment. There were no significant differences between the groups in psychiatric symptomatology or level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 13 publications
7
9
0
3
Order By: Relevance
“…The mothers in this study tended to be well educated women who held full-time jobs and were not experiencing marked financial difficulties, a finding that replicates earlier investigations of smaller, less diverse samples (Leiblum et al, 1995;Klock et al, 1996;Mannis 1999;Bock, 2000;Murray & Golombok, 2005a). Their decision to choose single motherhood was not taken lightly.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The mothers in this study tended to be well educated women who held full-time jobs and were not experiencing marked financial difficulties, a finding that replicates earlier investigations of smaller, less diverse samples (Leiblum et al, 1995;Klock et al, 1996;Mannis 1999;Bock, 2000;Murray & Golombok, 2005a). Their decision to choose single motherhood was not taken lightly.…”
Section: Discussionsupporting
confidence: 73%
“…Leiblum et al, 1995;Murray & Golombok, 2005a;Klock et al, 1996). Klock et al (1996) concluded that women seeking DI were financially secure, highly educated women who were psychologically similar to married mothers using DI to have a child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Una actitud contraria a "ir de caza" la encontramos -como se ha visto-en los discursos de nuestras entrevistadas, en las intervenciones de MSPE en foros on-line como los antes mencionados … y también en estudios realizados en el ámbito anglosajón, como el de Murray y Golombok (2005:251), cuyas entrevistadas enfatizaron también la inaceptabilidad ético-moral de esta opción, al igual que lo habían hecho antes otras mujeres estudiadas en ese mismo ámbito geográfico-cultural (Klock et al 1996;Mechanek et al 1988). La fecundación sexual planificada no declarada se sitúa, de hecho, en el peldaño inferior de la que puede ser llamada "escala de explicabilidad" de las distintas vías de acceso a la maternidad en solitario ("¿cómo le cuentas a un niño que engañaste a una persona?…”
Section: Resultados "Ir De Caza": Imágenes Sobre Las Mspe Que Acuden unclassified
“…Nevertheless, studies of anonymous sperm donation show that mothers' intentions to disclose are significantly higher in solo mother than in heterosexual couple families (Klock et al, 1996, Murray, Golombok, 2005), presumed to result from the need to explain the absence of a father (Brewaeys, 2010). A body of empirical evidence, however, is not yet available to support the claim that solo mothers actually disclose to their children at an early age or that they do so owing to the absence of a father in the home.…”
Section: Introductionmentioning
confidence: 99%